1986
DOI: 10.1159/000124634
|View full text |Cite
|
Sign up to set email alerts
|

Association of Diurnal Variations in Hypothalamic but Not Cortical Opiate ([<sup>3</sup>H]-Naloxone)-Binding Sites with the Ability of Naloxone to Induce LH Release in the Prepubertal Female Rat

Abstract: We report the existence of a diurnal variation in the binding of the opiate antagonist [3H]-naloxone to slices of the mediobasal hypothalamus from prepubertal female rats. The binding is highest in the early morning and reaches a nadir in the late afternoon. Opiate binding in cortical slices from such animals is constant over the course of the day. Changes in receptor density, and not in receptor affinity, account for the diurnal variation in the amount of ligand bound. These diurnal variations in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…A similar sexual dimorphism has bccn demonstrated for opiate (37) and muscarinic rcccptors (38). Thus, the steroid environment and the time of day are two important factors in thc regulation of PGE, receptors, as they are for other receptors (39)(40)(41).…”
Section: Discussionsupporting
confidence: 52%
“…A similar sexual dimorphism has bccn demonstrated for opiate (37) and muscarinic rcccptors (38). Thus, the steroid environment and the time of day are two important factors in thc regulation of PGE, receptors, as they are for other receptors (39)(40)(41).…”
Section: Discussionsupporting
confidence: 52%
“…Precedence for opioid receptor downregulation was provided by results in lactating rats, which were totally refractory to PRL stimulation by mor phine [47]. Moreover, the feasibility of opioid receptor downregulation occurring over short time periods is evi denced by a report showing a diurnal rhythm in the num ber of opioid receptors in immature female rats [48]. Finally, the concentration of PRL in the anterior pitu itary gland at any given time may affect the PRL response to exogenous P-End.…”
Section: Discussionmentioning
confidence: 99%
“…Diurnal variations in gonadotrophin release are clearly of importance in the attainment of reproductive competence (MacKinnon et al, 1978;Ojeda et al, 1986). Jacobson & Wilkinson (1986) have suggested that circadian variations in brain neurotransmitter binding sites (receptors; see also Wirz-Justice, 1987), and in particular hypothalamic opioid receptors, may entrain prepubertal hormone secretion. Since melatonin is now thought to be a timekeeping hormone (Karsch, 1986;Reiter, 1987), we wished to know whether the anti-pubertal effects of melatonin (Rivest et al, 1986;Lang, 1986) might be expressed as a disruption of hypothalamic opioid receptor binding rhythms.…”
Section: Introductionmentioning
confidence: 99%